STUDI PENERAPAN MODEL DELONE AND MCLEAN UNTUK MENGUKUR KESUKSESAN GENERATIVE AI DALAM OPERASIONAL UMKM DI JAKARTA - Nugroho, Rizky Ramadhani; Fadillah F, Nadya; Kasofi, Adnan (Yayasan Education and Social Center, 2025)
This study Aims to evaluate the success of Generative AI adoption by Micro, Small, and Medium Enterprises (MSMEs) in Jakarta using the DeLone and McLean model. Generative AI is utilized to enhance productivity, accelerate content creation, reduce operational costs, and strengthen customer interaction in the digital space. The research involved 372 MSME respondents who have integrated this technology into their business operations, and the data was analyzed using Structural Equation Modeling (SEM) with AMOS. The results show that System Quality and Information Quality have a significant impact on Usage and User Satisfaction, which in turn positively affect Net Benefits. These findings offer both theoretical insights and practical recommendations for optimizing the strategic use of Generative AI within urban MSME sectors.